The Opportunities of Cleaner Production in Carica (Carica pubescens) Industry to Reduce Hazardous Waste - Faradies Arija; P. Purwanto; H. Hadiyanto (BIORE Scientia Publisher, 2022)
Wonosobo regency had many small and medium industries which produced carica fruit into candied carica. In the process of making candied carica by using simple technology, there tented to be inefficient in the use of materials, energy and water. It raised the amount of waste which can cause economic loss and environmental. The implementation could be used as one of the efforts to improve efficiency is cleaner production. This study aimed to identify the process of inefficiencies at each stage in the process of production and to provide alternative opportunities of applying cleaner production in the process of making candied carica. The methods were the observation, direct measurement and interview. The results showed the alternative opportunities of applying cleaner production that uses container vessel while charging syrup in the packaging process and the filtering process results boiling syrup; the application of operational standards of production use of tools and materials; application of good housekeeping; the separation between the solid and liquid waste; reuse used water from sinks, leather waste utilization for composting. The benefits of economic and environmental that derived from the application of cleaner production is the use of container vessel in the packaging process and filtered the boiled syrup IDR. 1,200,000 savings/ month and reduced liquid waste as much as 240 liters/ month. Reuse of washing water used could save IDR. 380,424/ month and reduce liquid waste as much as 110.268 liters / month. Utilization of the skin as compost obtained profits IDR. 2,220,000/ month and reduced solid waste 3,600 kg/ month. Thus, the implementation of cleaner production improved economic and environmental benefits of reduced waste formation